Understanding initial undergraduate expectations and identity in computing studies. (4th March 2018) - Kinnunen, Päivi; Butler, Matthew; Morgan, Michael; Nylen, Aletta; Peters, Anne-Kathrin; Sinclair, Jane; Kalvala, Sara; Pesonen, Erkki
ABSTRACT: There is growing appreciation of the importance of understanding the student perspective in Higher Education (HE) at both institutional and international levels. This is particularly important in Science, Technology, Engineering and Mathematics subjects such as Computer Science (CS) and Engineering in which industry needs are high but so are student dropout rates. An important factor to consider is the management of students' initial expectations of university study and career. This paper reports on a study of CS first-year students' expectations across three European countries using qualitative data from student surveys and essays. Expectation is examined from both short-term (topics to be studied) and long-term (career goals) perspectives. Tackling these issues will help paint a picture of computing education through students' eyes and explore their vision of its and their role in society. It will also help educators prepare students more effectively for university study and to improve the student experience.